PENGARUH SISTEM INFORMASI MANAJEMEN KEPEGAWAIAN TERHADAP PERENCANAAN SUMBER DAYA MANUSIA PADA BADAN KEPEGAWAIAN DAERAH KABUPATEN SIKKA - Mado, Yohanes Jibrail; Mado, Theresia Wihelmina (HOAQ (High Education of Organization Archive Quality) : Jurnal Teknologi Informasi, 2019)
The purpose of this study is to find out whether there is the influence of the Civil Service Management Information System on Human Resource Planning at the Regional Personnel Agency of Sikka District. The design of the research used is descriptive and comparative causal research through surveys. The purpose of descriptive research is to make a systematic, factual and accurate explanation of the facts and characteristics of a particular population or region. The technique of data collection is done by spreading questionnaires to n respondents to get answers that are in accordance with the research variables, as material to prove the proposed hypothesis. The sample in this study were 54 people. From the results of this study it was found that SIMPEG had a significant effect on HR planning in the Sikka City Personnel Agency. This study recommends that the Sikka District Personnel Agency that in implementing HR Planning can be carried out properly, if using accurate and accurate information. Such accurate and accurate information can be generated if SIMPEG supporting indicators are adequate and together work at the expected level.